2019
DOI: 10.5455/javar.2019.f327
|View full text |Cite
|
Sign up to set email alerts
|

Phenotypic detection of methicillin-resistant Staphylococcus aureus in village chickens from poultry markets in Maiduguri, Nigeria

Abstract: Objective: The study was carried out to detect the carriage of methicillin-resistant Staphylococcus aureus (MRSA) and their antimicrobial susceptibilities in village chickens sold at Maiduguri poultry markets using phenotypic characterization. Materials and Methods: This was a cross-sectional study where 120 samples comprised 50% each of Nasal and cloacal swabs, were, respectively, collected from live village chickens sold at Maiduguri poultry… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
9
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 27 publications
2
9
2
Order By: Relevance
“…The present study showed that erythromycin, cefoxitin, and ceftazidime were the antimicrobial agents with the highest antibiotic resistance rates. This finding is similar to reports by others [13,20,21] . Erythromycin is an inexpensive and available antimicrobial agent in Nigeria [15] .…”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…The present study showed that erythromycin, cefoxitin, and ceftazidime were the antimicrobial agents with the highest antibiotic resistance rates. This finding is similar to reports by others [13,20,21] . Erythromycin is an inexpensive and available antimicrobial agent in Nigeria [15] .…”
Section: Discussionsupporting
confidence: 94%
“…During the six-month study, from February to July 2018, 38 phenotypically confirmed MRSA strains that were isolated from the nasal swabs of consenting participants (eight inpatients, 11 outpatients, and 19 healthcare workers) after receipt of ethical approval from the review board of Sokoto State ministry of health under approval number SMH/1580/V.IV. Resistance to methicillin by the isolates was confirmed by the oxacillin resistance screening agar base test [12,13] .…”
Section: Methodsmentioning
confidence: 99%
“…Poor hygiene and crowding facilitate the easy transmission and fast spread of pathogens via direct and indirect contact. Earlier studies have reported the presence of S. aureus , including MRSA, in live bird and chicken carcasses at poultry markets in Zaria [ 20 ] and Maiduguri [ 9 ] in northern Nigeria. A high prevalence (80.0%) of S. aureus was reported in samples from live chicken among small holder farms in Zaria [ 21 ], while Nworie et al [ 8 ] reported a low MRSA prevalence (0.8%) in poultry farms in Ebonyi State, southeastern Nigeria.…”
Section: Discussionmentioning
confidence: 99%
“…Regrettably, there are few data about MRSA, its molecular properties and the transmission routes, especially via meat production and marketing chains from low-income countries, like Nigeria. Earlier studies under separate investigations have documented the detection of MRSA in samples of human [ 6 , 7 ] and animal origin [ 8 , 9 ]. Continuous surveillance using the latest technology will provide in-depth analysis of MRSA profiles for a better understanding of the origins and dissemination patterns in human and animal populations across different geographical locations.…”
Section: Introductionmentioning
confidence: 99%
“…Among the most important MDR bacteria, the “ESKAPE” group encompassing Enterococcus faecium , Staphylococcus aureus , Klebsiella pneumoniae , Acinetobacter baumannii , Pseudomonas aeruginosa , and Enterobacter strains can escape the biocidal action of most antimicrobial agents [ 10 ]. In the poultry industry, a steadily increasing level of MDR bacteria has also been reported, for example of Escherichia coli [ 11 ], Campylobacter [ 12 , 13 , 14 ], Salmonella [ 15 , 16 ], and methicillin-resistant S. aureus (MRSA) [ 17 , 18 ].…”
Section: Introductionmentioning
confidence: 99%